Zn(ii)-Curcumin supplementation alleviates gut dysbiosis and zinc dyshomeostasis during doxorubicin-induced cardiotoxicity in rats. Issue 9 (21st August 2019) - Wu, Rihui; Mei, Xueting; Wang, Jiasheng; Sun, Wenjia; Xue, Ting; Lin, Caixia; Xu, Donghui
Abstract : Dietary Zn(ii )-curcumin protects against doxorubicin-induced cardiomyopathy by modulation of the gut microbiota and maintenance of zinc homeostasis. Abstract : Doxorubicin is a powerful anticancer agent used to treat a variety of human neoplasms. However, the clinical use of doxorubicin is hampered by cardiotoxicity and effective cardioprotective adjuvants do not exist. Dietary zinc, an essential nutrient, is required to maintain steady-state tissue zinc levels and intestinal homeostasis and may yield therapeutic benefits in diseases associated with zinc dysregulation or gut dysbiosis. Here, we investigated the effects of dietary Zn(ii )-curcumin (ZnCM) solid dispersions on gut dysbiosis and zinc dyshomeostasis during doxorubicin-induced cardiotoxicity in rats. Rats were injected with multiple low doses of doxorubicin and orally administered ZnCM daily over four weeks. Daily administration of ZnCM not only alleviated Dox-induced gut dysbiosis—as indicated by the increased Firmicutes -to- Bacteroidetes ratio and the maintenance of the relative abundances of major beneficial bacteria including Clostridium_XIVa, Clostridium_IV, Roseburia, Butyricicoccus and Akkermansia —but also maintained intestinal barrier integrity and decreased the lipopolysaccharide (LPS) contents of feces and plasma. ZnCM also significantly attenuated doxorubicin-induced zinc dyshomeostasis, which was mirrored by preservation of zinc levels and expression of zinc-related transporters. Furthermore, ZnCM significantly improved heart function and reduced cardiomyocyte apoptosis and myocardial injury in doxorubicin-treated rats. Notably, the regulation of zinc homeostasis and cardioprotective and microbiota-modulating effects of ZnCM were transmissible through horizontal feces transfer from ZnCM-treated rats to normal rats. Thus, ZnCM supplementation has potential as an effective therapeutic strategy to alleviate gut dysbiosis and zinc dyshomeostasis during doxorubicin-induced cardiotoxicity.